Analisis Keterampilan Guru dalam Pengelolaan Kelas pada Mata Pelajaran Tematik Kelas IV SDIT Darussalam Deli Tua - Nila Lestari; Sukmawarti Sukmawarti; Hasanah Hasanah (Journal on Education, 2023)
This study aims to describe the teacher's ability to manage classes in thematic subjects in class IV SDIT Darussalam. This type of research is descriptive qualitative. This research was conducted at SDIT Darussalam Deli Tua Village, Kab. Deli Serdang, the subject of this study was the fifth grade teacher at SDIT Darussalam. The instruments in this study were observation sheets, interview sheets and documentation. In analyzing the data, the researcher uses an inductive pattern, namely data reduction, data presentation, and drawing conclusions. The results of this study are that in classroom management the teacher always prepares learning tools such as lesson plans, learning resources and learning media, but teachers do not use various classroom management approaches and student-centered learning models. The conclusion in classroom management is that there are also obstacles experienced by teachers, namely internal and external factors, where external factors are student learning facilities, learning environment and teacher insight in understanding student needs. Internal factors are personality related to students' social-emotional as well as students' family background can also be an obstacle to effective classroom management in learning mathematics in class V SDIT Darussalam